2011
DOI: 10.1002/pssb.201046531
|View full text |Cite
|
Sign up to set email alerts
|

Mg and Si dopant incorporation and segregation in GaN

Abstract: The surface segregation of Mg and Si dopant species and their atomic incorporation sites in GaN films grown by metal-organic vapour phase epitaxy (MOVPE) on sapphire (0001) substrates have been analysed by X-ray photoemission spectro-microscopy and X-ray standing waves (XSW). As revealed by spectro-microscopy, both Mg and Si tend to segregate to the surface. In case of Mg, an enhanced surface dopant concentration is found even after sputter-removal of several tens of nanometres, which confirms a segregation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The implantation of zinc ions does not change the E3 concentration in HT bulk ZnO. [49] The same result was reported for ZnO thin films: the implantation of zinc [38] or nickel ions [46] had no impact on the E3 defect density. Gu et al reported an increase of the E3 concentration in MG bulk ZnO samples after nitrogen ion implantation.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…The implantation of zinc ions does not change the E3 concentration in HT bulk ZnO. [49] The same result was reported for ZnO thin films: the implantation of zinc [38] or nickel ions [46] had no impact on the E3 defect density. Gu et al reported an increase of the E3 concentration in MG bulk ZnO samples after nitrogen ion implantation.…”
Section: Introductionsupporting
confidence: 61%
“…We have characterized the properties of the deep level defect E3 in several earlier investigations. [16,19,28,33,36,38,42,46,48,53,56,63,82] In these experiments bulk samples obtained from Tokyo Denpa as well as heteroepitaxial thin films grown by pulsed laser deposition were used. Overall, about a hundred samples containing the E3 center were and are available.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the loss mechanism is not present for the Schottky reference structure, the defect in question must be specifically related to the usage of NiO. Ni as an impurity in ZnO has been investigated, e.g., by Schmidt et al [35] where the authors show Ni incorporation to lead to the formation of an electronically defect having two detectable charge transistion within the ZnO band gap. The deeper of these two can be (de-)populated by UV photons.…”
Section: Transparent Uv-active Solar Cells Based Onmentioning
confidence: 99%